Electricity price forecasting on the day-ahead market using machine learning - Tschora, Léonard; Pierre, Erwan; Plantevit, Marc; Robardet, Céline (Applied energy, 2022)
The price of electricity on the European market is very volatile. This is due both to its mode of production by different sources, each with its own constraints (volume of production, dependence on the weather, or production inertia), and by the difficulty of its storage. Being able to predict the prices of the next day is an important issue, to allow the development of intelligent uses of electricity. In this article, we investigate the capabilities of different machine learning techniques to accurately predict electricity prices. Specifically, we extend current state-of-the-art approaches by considering previously unused predictive features such as price histories of neighboring countries. We show that these features significantly improve the quality of forecasts, even in the current period when sudden changes are occurring. We also develop an analysis of the contribution of the different features in model prediction using Shap values, in order to shed light on how models make their prediction and to build user confidence in models. •Evaluation of several machine learning models for electricity price forecasting.•Methodology is rigorously detailed, the source and the data are made available.•New Machine Learning models are provided and achieved cutting edge results.•Performances of the models are increased by adding new features to the datasets.•XAI techniques are used to explain which features impact most the predictions.•Modeling multiple countries at once improves results.